Transcriptomics integrated with metabolomics reveals the effect of regulated deficit irrigation on anthocyanin biosynthesis in Cabernet Sauvignon grape berries. (1st June 2020) - Yang, Bohan; He, Shuang; Liu, Yuan; Liu, Buchun; Ju, Yanlun; Kang, Dengzhao; Sun, Xiangyu; Fang, Yulin
Graphical abstract: Highlights: Effects of RDI on anthocyanin biosynthesis in wine grapes was investigated. RDI1 treatment increased anthocyanin content most effectively. Revealing the changes of genes and substances under RDI by Omics. Mapping the effects of anthocyanin biosynthetic pathway under RDI. Abstract: Regulated deficit irrigation (RDI) is a new type of water-saving irrigation technology developed in recent years which was well suited to arid and semi-arid grape plant areas. The anthocyanin synthesis of grapes under RDI was revealed through omics in this study. RDI slightly decreased the hundred-grain weight and increased the soluble solid content, juice pH, reducing sugar content, and total anthocyanin content. Meanwhile, the total acid content decreased before ripening. Transcriptomics and metabolomics analyses revealed that large numbers of differentially expressed genes (DEGs) and significantly changed metabolites (SCMs) were filtered in the RDI groups. RDI1 with 30% ETc upregulated 7 related gene expression levels in the anthocyanin biosynthetic pathway and also increased some metabolites contents. Eventually, the contents of most monomeric anthocyanins in the RDI groups were increased, and the proportion of Mv increased in the ripe grapes of the RDI groups. In all, RDI is a useful water-saving irrigation method which could also increase anthocyanin content in grapes.